Group decision and negotiation in an uncertain world : 18th International Conference, GDN 2018, Nanjing, China, June 9-13, 2018, Proceedings /: 18th International Conference, GDN 2018, Nanjing, China, June 9-13, 2018, Proceedings. (2018) - Unknown
No abstract available